Comparison of Radiological Features and Clinical Characteristics in Scoliosis Patients With Chiari I Malformation and Idiopathic Syringomyelia: A Matched Study. Issue 23 (1st December 2019) - Shen, Jianxiong; Tan, Haining; Chen, Chong; Zhang, Jianguo; Lin, Youxi; Rong, Tianhua; Jiao, Yang; Liang, Jinqian; Li, Zheng
Abstract : Study Design: Retrospective study. Objective: To compare syrinx characteristics, scoliotic parameters, and neurological deficits between Chiari I malformation (CIM) and idiopathic syringomyelia (IS) in the scoliotic population. Summary of Background Data: CIM and IS are common in neuromuscular scoliosis patients; however, differences in syrinx characteristics, scoliotic parameters, and neurological deficits between CIM and IS are unclear. Methods: Thirty-six patients with scoliosis secondary to CIM were enrolled retrospectively and matched with 36 IS patients for sex, age, scoliosis classification, and Cobb angle. Information on radiographic features of scoliosis and syrinx and neurological deficits was systematically collected. Results: Sex, age, and coronal, and sagittal scoliosis parameters did not differ between the CIM and IS groups. The CIM group had a longer syrinx (12.9 ± 4.0 vertebral levels vs. 8.7 ± 5.5 vertebral levels, P  < 0.001), a higher cranial extent (3.6 ± 2.2 vs. 5.2 ± 3.5, P  = 0.027), and a lower caudal extent (15.6 ± 2.9 vs. 13.0 ± 4.6, P  = 0.006) than the IS group, despite no differences in syrinx/cord (S/C) ratio or syrinx classification. No differences in neurological deficits were identified between the CIM and IS patients. Conclusion: With demographic and scoliotic coronal parameters matched, the CIM patients had a longer syrinx, located at a higher cranial and lower caudal level, compared with the IS group. No significant differences in syrinx S/C ratio, sagittal features of scoliosis, or neurological deficits were detected between the two groups. Level of Evidence: 3 Abstract : The differences in syrinx characteristics, scoliotic parameters, and neurological deficits between Chiari I malformation (CIM) and idiopathic syringomyelia (IS) are unclear. This retrospective study found the CIM patients had a longer syrinx, located at a higher cranial and lower caudal level, compared with the IS group.